Laparoscopic management of a small bowel obstruction: paraduodenal hernia - Govindaraj, Shrenik; Govindaraj, Sridar; Newton, Mario Victor; Prakash, Clement (International Surgery Journal, 2020)
Paraduodenal hernia are very rare but the commonest internal hernia. Left paraduodenal hernia is due to herniation of the small bowel into the fossa of Landzert. The fossa results from a combination of failure of fusion of the small bowel mesentery with the retro peritoneum and malrotation of the midgut. Here we present a 27 years lady who saw multiple consultants with varied presentations and underwent extensive investigations over a one-year period, with one consultant referring her to a psychiatrist for malingering. CT scan revealed a foramen of Winslow hernia. The radiologist has to be aware of the CT findings of this unusual hernia. At laparoscopy, it was a left paraduodenal containing small bowel. We reduced the contents and plicated the sac with closure of the mouth. Patient did well and was discharged on 3rd post-operative day. On follow up she is doing well.